STOX1: Key Player in Trophoblast Dysfunction Underlying Early Onset Preeclampsia with Growth Retardation - Marie van Dijk; Cees B. M. Oudejans (Journal of Pregnancy)
Currently, only two preeclampsia susceptibility genes (ACVR2A, STOX1) have been identified within confirmed regions with significant genome-wide linkage, although many genetic screens in multiple populations have been performed. In this paper, we focus on the STOX1 gene. The epigenetic status of this gene is discussed explaining the maternal transmission of the STOX1 susceptibility allele observed in preeclamptic families. The known upstream regulation and downstream effector genes of the transcription factor STOX1 are described. Finally, we propose a model in which we combine the cell type-specific and allele-specific effects of STOX1. This includes intrinsic effects (differential CpG island methylation) and extrinsic effects (regulation of effector genes).